Immersive Virtual Reality Exposure Therapy for Social Phobia among Management Students - D.M. Arvind Mallik, (h.c). (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: human’s ire social creatures. We intend to bond with friends, engage with coworkers, and interfere in relationships. Besides, we indeed interact with other people, but for students with social anxiety disorder (especially stage fear), it may have a way to make them feel inferior, which may result in stress and anxiety. It is this where the virtual ideality therapy icon helps.Research Methodology-Final Year Management Students with the principal diagnosis of social anxiety disorder (those who have stage fright) were identified randomly and were recruited from the class of 25 chosen as volunteers with an age gap of average 21 (age group 21-22). An explanatory research design was involved with participants assigned into and completed 8 sessions of manualized virtual ideality exposure therapy. Standardized self-report measures were collected and analyzed in pretreatment and posttreatment, and diagnostic status was reassessed for the 3-month follow-up. Findings: Our study results indicated that Virtual reality exposure therapy positively impacts MBA final year Students who have experienced Social anxiety (stage fear) drastically decreased over a period of time, confidentiallyConclusion: Virtual reality exposure therapy resulted in regaining the lost confidence among chosen students. Early detection and intervention is highly recommended to help them and with Immersive VR can play a major role in eradicating students with fear of public speaking which can be implemented at institute level which is simple, cost-effective and drastically will improve their confidence level provided Institutional support guaranteed by becoming an Innovative solution of Current Research by using futuristic emerging Technology